IMPACT OF SOCIOECONOMIC VULNERABILITY ON COVID-19 OUTCOMES AND SOCIAL DISTANCING IN BRAZIL - Lins Filho, Paulo Cardoso (2023)
Due to the persistently high cases and deaths, Brazil became one of the worst countries affected by the COVID-19 pandemic. Understanding the possible health inequities is essential, given the population's diversity and the country's fragile socioeconomic situation. Thus, this study aimed to assess the impact and correlation of socioeconomic vulnerability on COVID-19 outcomes and social distancing in Brazil. The Gini Coefficient (GC), the Social Vulnerability Index (SVI), epidemiological data on the COVID-19 epidemic in Brazil, and the Social Distancing Index (SDI) were retrieved from online databases and assessed for each Brazilian state. Data was statistically analyzed through non-parametric tests and multiple linear regressions. The mean values for the GC and SVI were 0.495 and 0.261, respectively. A positive statistically significant correlation was found between the socioeconomic indicators and the three variables related to the COVID-19 outbreak. States with very low social vulnerability presented fewer deaths per 100 thousand inhabitants due to COVID-19 than states with moderate social vulnerability. SVI was a predictor of accumulated cases, confirmed deaths, and social distancing. The COVID-19 outcomes and SDI in Brazilian states are correlated to socioeconomic conditions. The pandemic impacts are more severe on less favored communities.